Pengaruh strategi inovasi dan orientasi pasar terhadap keunggulan bersaing dan kinerja perusahaan (studi pada UKM OKE OCE Jakarta) - Mulyono, Sri (CV. Kurnia Grup, 2024)
The DKI Jakarta Provincial Government program, OK OCE (One District, One Entrepreneurship Center), was pioneered by Anies Baswedan and Sandiaga Uno. The aim is to assist micro, small and medium enterprises (MSMEs) in cultivating an entrepreneurial spirit through the Cooperatives and MSMEs Sub-Department. The main objective of this program is to realize an economic mission that prioritizes society, justice, prosperity, quality and broad insight. This research aims to show and analyze three ways in which innovation strategy and market orientation influence the performance of OK OCE SME companies in Jakarta: through competitive advantage, directly and indirectly, through innovation strategy and market orientation. All SMEs partnering with OK OCE in Jakarta are research subjects. Data were analyzed using SEM-PLS. The total research sample was 100 small and medium business owners in OK OCE Jakarta, and the simple random sampling method was used for probability sampling. Based on the findings of this research, (1) Although innovation strategies SMEs in OK OCE Jakarta gain a competitive advantage, this does not directly improve their performance; (2) The increase in the performance of SMEs in OK OCE Jakarta is not a direct result of market orientation, but rather the result of competitive advantage. 3 The increase in the performance of SMEs in OK OCE Jakarta is significantly influenced by innovation strategy and market orientation.